2023
DOI: 10.1021/acsanm.3c01183
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Sensitive Detection of Formaldehyde at Room Temperature by Tin Oxide Nanoparticles/Reduced Graphene Oxide Composite

Abstract: A highly selective formaldehyde (HCHO) gas sensor using a tin oxide nanoparticles−reduced graphene oxide (rGO−SnO 2 ) composite has been fabricated and investigated for room-temperature sensing. The rGO−SnO 2 composite is synthesized by cost-effective wet chemical method. The fabricated sensor exhibits remarkable sensing performance, including a higher response, a low detection limit of ≈33 ppb (theoretical), good selectivity, and long-term stability. Furthermore, the effects of humidity level and calcination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…reported that during the ripening of tamarillo fruit, the concentration of total VOCs increased by four times, and among them, phenols and terpenoids were the main components . Kashyap et al assessed the selective and sensitive detection of formaldehyde at room temperature using tin oxide nanoparticles/reduced graphene oxide composites . Li et al investigated biogenic VOC emissions from apple and peach tree leaves and fruits throughout the fruit development process, aiming to understand the patterns and factors influencing the VOC release .…”
Section: Introductionmentioning
confidence: 99%
“…reported that during the ripening of tamarillo fruit, the concentration of total VOCs increased by four times, and among them, phenols and terpenoids were the main components . Kashyap et al assessed the selective and sensitive detection of formaldehyde at room temperature using tin oxide nanoparticles/reduced graphene oxide composites . Li et al investigated biogenic VOC emissions from apple and peach tree leaves and fruits throughout the fruit development process, aiming to understand the patterns and factors influencing the VOC release .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the environmental problems related to the EC, this work pursues an alternative to detect and remove the drug o oxacin (OFL) in a simple, fast, and inexpensive way using of two adsorbents, zinc stannate (Zn 2 SnO 4 ) and reduced graphene oxide (rGO), because both the surfaces possess numerous applications in adsorptive process [18][19][20][21]. To better understand the stability and spontaneity of the adsorption process of OFL in both compounds (zinc stannate and reduced graphene oxide), theoretical calculations involving adsorption energy were performed [19,22,23].…”
Section: Introductionmentioning
confidence: 99%